A Probabilistic Framework for the Fatigue Damage Assessment of Ships Navigating through Level Ice Fields. (June 2021) - Zhao, Weidong; Leira, Bernt Johan; Kim, Ekaterina; Feng, Guoqing; Sinsabvarodom, Chana
Highlights: A fatigue damage analysis procedure based on the application of numerical simulation tools is proposed for ships advancing in level ice fields. The applicability of the procedure is illustrated using a hypothetical scenario with the Xuelong 2 icebreaker The results show that the fatigue damage predicted by the proposed procedure is sensitive to boundary conditions, ship properties, and S-N curves. Abstract: For ships navigating in ice-covered waters, fatigue damage due to ice loads is an important issue. The purpose of this paper is to provide ship researchers and engineers with a simulation-based procedure for a probabilistic fatigue damage assessment of ships moving through a level ice field. A novel procedure for fatigue damage assessment using numerical simulations is developed, and a hypothetical scenario with the Xuelong 2 icebreaker is used to illustrate the procedure. Long-duration time-domain simulations are performed to generate samples of the ice-load peaks due to ship-ice interactions. Based on the average conditional exceedance rate (ACER) method, the extreme value statistics of the line load peaks are predicted, and subsequently, the fatigue stresses caused by ice loads are estimated by means of beam theory. Several analytical models are applied to describe the probability distribution of the stress amplitudes, and the fatigue damage is calculated based on S-N curves and the Palmgren-Miner formula. Furthermore, a quantification of the effects of uncertainties related to discretization errors (mesh size, reference period), ship-model properties, choice of boundary conditions, and S-N curves is performed.